Effect of Re-Application of Microbrush on Micro Tensile Bond Strength of an Adhesive to Dentin - Seied Majid Mosavi Nasab; Abdolrahim Davari; Alireza Danesh Kazemi; Ehsan Geravand (Tehran University of Medical Sciences, 2013)
Background and Aims: Re-application of microbrush may affect the micro tensile bond strength of adhesives to dentin. The aim of this study was to evaluate the effect of re-application of microbrushes on the micro tensile bond strength of an adhesive to dentin.Materials and Methods: Thirty freshly extracted molars teeth were collected and enamel of occlusal surface were removed to expose superficial dentin. Then superficial dentin was etched, washed and partially air dried.According to the times of application of microbrush, teeth were divided into two test groups. In group 1, newmicrobrushs were used, but in group 2, the ones that were already used for twice were included. Ambar dentin bonding agent (FGM/Brazil) was applied to the etched dentin with microbrushes according to the manufacturer's instructions. Then the crown of teeth was built up with LLiss (FGM/Brazil) composite resin. The teeth were sectioned in buccolingual direction to obtain 1mm slabs. Then 50 hourglass- shape samples were made from 30 teeth (25 Specimens per group). The microtensile bond strength of the specimens was tested using MTD500 (SD Mechatronik, Germany). The data were statistically analyzed by T-test.Results: The mean values for the microtensile bond strength were 30.49±7.18 and 23.61±9.06 MPa±SD for the first and second groups, respectively. There was significant difference between the groups (P=0.005).Conclusion: Microbrushes should not be used for more than one cavity preparation.